A Retrospective Study: Risk Factor Analysis of Secondary Bacterial Infection in Pediatric Atopic Dermatitis Patients - Desiana Widityaning Sari; Sawitri Sawitri; Muhammad Yulianto Listiawan; Dwi Murtiastutik; Linda Astari; Alpha Fardah Athiyyah; Afif Nurul Hidayati (Faculty of Medicine, Universitas Airlangga, 2021)
Background: Atopic Dermatitis (AD) is a complex multifactorial disease that includes defects in skin architecture, immune dysregulation, and changes of skin flora, and it predominantly occurs in infancy and childhood. The defects in skin barrier structures are mentioned as one of the factors that facilitates bacterial colonization. Bacterial infection in AD can worsen the inflammation. It requires treatment with antibiotics, which takes longer therapy time, higher costs, and ultimately affects the patient’s quality of life and his/her family members. Purpose: To find out the epidemiology, diagnosis, management of AD, and analyze the risk factors of secondary bacterial infection in new AD patients at the Pediatric Dermatology Division, Dermatovenereology Outpatient Clinic, Dr. Soetomo General Academic Hospital. Methods: This was a retrospective study with a total sampling method. The research data were medical records of new AD patients at the Pediatric Dermatology Division, Dermatovenereology Outpatient Clinic, Dr. Soetomo General Academic Hospital Surabaya from January 2012 to December 2018. Result: There were 404 new patients with AD at the Pediatric Dermatology Division from January 2012 to December 2018, and 210 of them were accompanied by secondary bacterial infection. There was a correlation between a history of dry skin (p=0.000) with the incidence of secondary bacterial infection in AD patients. Conclusion: In this study, AD patients with a history of dry skin had a risk of complication such as bacterial secondary infection.